POSITIVISM AND ITS RELEVANCE ON ISLAMIC EDUCATION IN HIGHER EDUCATION (International Conference on Social and Islamic Studies, 2021)
The purpose of this article is to examine the philosophy of positivism initiated by Auguste Comte and to trace how his philosophical ideas influence the development of the paradigmof Islamic education in Indonesia. This research is a type of library research, which is aseries of activities related to the methods of collecting library data, reading, and taking notes, and processing research materials. Through descriptive-interpretive analysis, this article argues that the philosophy of positivism has not succeeded in removing religion from human life in the world. However, the paradigm of thinking that he introduced substantially contributed to reorienting the paradigm of Islamic education in higher education from a theological orientation to an integrative orientation. The relevance of positivism in Islamic education can be seen in educational research and the integration of Islamic sciences in Islamic higher education.